Influence of shelf-life duration on mechanical, thermal and shape recovery motion derivatives of shape memory polyurethane - Vasavi, Boggarapu (2024)
Shape memory polymer is widely used in bio-medical applications such as stents, sutures, drug delivery etc., However, the shape recovery behavior and mechanical properties in these applications are crucial and may be affected during shelf storage. The present research, therefore explores the effect of shelf life on mechanical, thermal and shape recovery performance of polyurethane (PU) based shape memory polymer (SMP). Experimental samples S1, S3, S5 and S10 were prepared from polymer pellets that were stored for 1,3,5 and 10-year time duration respectively. FTIR analysis revealed that samples underwent degradation due to chain scissions influencing their performance. The results indicated that tensile and flexural strength decreased by 35.16 % and 29.3 % respectively, from S1 to S10. Fracture surfaces were examined under Scanning Electron Microscopy to identify the failure features. In addition, Differential scanning calorimetry (DSC)exhibited a decrease in glass transition temperature (Tg) from S1 to S10, resulting in a corresponding reduction in the rate of shape restoration. An in-depth analysis is conducted to investigate the relationship between polymer aging and the shape recovery behavior. Finally, the shape recovery motion curves in terms of displacement, velocity and acceleration concerning the time for all the specimens were also discussed in this study.